The Profiling of DNA Methylation and Its Regulation on Divergent Tenderness in Angus Beef Cattle - Zhao, Chunping; Ji, Guanyu; Carrillo, José A.; Li, Yaokun; Tian, Fei; Baldwin, Ransom L.; Zan, Linsen; Song, Jiuzhou (Frontiers in Genetics, 2020)
Beef is an important food sources in the world. Beef quality, especially tenderness, has significant impact on consumer satisfaction and industry profit. Most research to date has focused on the exploration physiological and developmental mechanisms of beef tenderness, but the role and impact of DNA methylation status on beef tenderness has yet to be elucidated. In this study, we exhaustively analyzed the DNA methylation status in divergent tenderness observed in Angus beef. We characterized the methylation profiles related to beef tenderness and explored DNA methylation distributions on the whole genome. As a result, differentially methylated regions (DMRs) associated with tenderness and toughness of beef were identified. Importantly, we have annotated these DMRs on bovine genome and explored bio-pathways of underlying genes and methylation biomarkers in beef quality. Specifically, we observed that the ATP binding cassette subfamily and myosin related genes were highly methylated gene sets, and generation of neurons, regulation of GTPase activity, ion transport and anion transport, etc., were the significant pathways related with beef tenderness. Moreover, we explored the relationship between DNA methylation and gene expression in DMRs. Some DNA methylated genes, such as MYH8, were identified as candidate biomarkers for beef tenderness. This study describes in depth the DNA methylome profiling related to beef tenderness and provides novel epigenetic information associated with beef quality, and which provide greater insight into meat science and help us further explore the mechanism of muscle biology.